Assistance Skills Competency Test Activities (UKK) Software Engineering Department in SMK Negeri 6 Jember - Wiwik Suharso (Kontribusia : Research Dissemination for Community Development, 2018)
The goal of this community engagement is to foster private Vocational Schools in the implementation ofCompetency Skills Test (UKK) Department of Software Engineering (RPL). The selected vocational practice exam is Package 3 on Car Rental App Design. The main activities of community service are accompaniment of implementation preparation, product assessment activities of vocational practice, and monitoring and evaluation (monev) value of competency achievement result. The objective of the preparation is to ensure the readiness of the implementing elements of both schools, learners’ understanding of the selected package and the preparation of laboratory infrastructure for hardware, software, network, and electrical installation. The purpose of the assessment is to provide students with a certain level of competency. While the objective of monev is to evaluate the results of achievements and feedback on improvements in the implementation of the following year. Execution preparation activities are conducted by SMK Sub-Rayon and monitored by the External Examiners (Dunia Usaha Dunia Industri or DUDI). While the assessment activities conducted by the Internal Examiners and DUDI from the University of Muhammadiyah Jember and the State Polytechnic of Jember. DUDI involvement has become a requirement in the guideline of UKK implementation of National Education Standards Agency (BSNP). In addition, DUDI is expected to maintain independence and professionalism in assessing the level of competence achieved by students, and the form of recognition from competent external agencies. From the assessment by DUDI stated that the students who pass pure as much as 171 or 95,53%, passed remedial as much as 2 or 1,12% and student do notpass as much as 6 or 3,35%. The non-graduation is due to the low achievement of the competency level, and some of the students do not take the exam.